Understanding tourism consciousness through habitus: perspectives of 'poor' black South Africans. Issue 3 (2nd September 2019) - Musavengane, Regis
Abstract : This paper established the existence of tourism consciousness among poor Black South Africans. Guided by Bourdieu's (1990) concept of habitus, meta-synthesis informed the qualitative approach used in the study where random face-to-face interviews were conducted with respondents in select South African 'poor' black communities/townships in Cape Town and Johannesburg. It is argued that although most Black South Africans are regarded as poor and seem to lack the means to engage in tourism, their consciousness regarding tourism is informed by five main factors: (i) structural exclusion, (ii) racialized spaces, (iii) the will to travel, (iv) tourism awareness, and (v) business ownership skills. Combined, these factors shape the consciousness of poor Black South Africans on tourism and inform their participation in the tourism system.